Presence of Germination Inhibitors in the Leaf Leachates of some Farm Grown Trees - Sharma, K.; Dhinora, K. K. (Indian Forester, 1987)
>Laboratory studies were conducted during 1986 to study the effect of four commonly grown farm trees (Acacia nilotica, Eucalyptus hybrid, Dallbergia sissoo and Morus alba) on germination and seedling growth of four rabr crops (Wheat, Rays, Field Pea and Lentil). Different water leacbates responded differently to each crop. Maximum reduction in germination and GRI WaS observed in Raya with all the leachates. Mulberry leachate. Had maximum toxic effect on all crops. Root length, shoot length, dry weight and vigour index Were reduced in all crops by the leachates of all tree spp. As compared to control. The degree of toxicity of leachates on these crops was in tbe order of Mulberry > Shisham > Eucalyptus > Klkar.